Contemporary Political and Media Discourses on Immigrants: A Review of Discourse Analytical Research in Spain - Stuardo-Concha, Miguel; Soler-Campo, Sandra; Riera-Retamero, Marina (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
In this research we review academic publications on media and political discourse about migration published in Spain between 2014 and 2019. The review has been carried out following the principles of the Rapid Review and Rapid Evidence Assessment of the Literature applied to discourse analytical research. The researchers have posed three main questions: a) Which representation of migrants and migration has been described in Spain during the last 5 years? b) Which particularities can be observed in the representation of migrant women? c) How are migrant children represented? Once the selection criteria have been applied, a final corpus of 18 recents publications has been selected. The researchers have found diverse and complex nuances in the discourse about immigration in Spain, both in the media and in political discourse. There are also relevant silences in the sphere of media discourse and little research addressing specifically the discourse on migrant women, children and the contemporary anti-migration discourse in the media and political sphere.